2020
DOI: 10.18506/anemon.765378
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Primary School Pre-service Teachers' Teaching Strategies about the Sum of Fractions

Abstract: Bu araştırmada, sınıf öğretmenliği programı 3. sınıf öğrencilerinin 2/7+1 3/7 şeklindeki bir soruyla kesirlerde toplama işleminin öğretimine yönelik farklı stratejilerinin incelenmesi amaçlanmıştır. Bir devlet üniversitesinde öğrenim gören 46 sınıf öğretmeni adayının katıldığı bu çalışmada nitel araştırma desenlerinden biri olan durum çalışması kullanılmıştır. Verilerin analizinde içerik ve betimsel analiz kullanılmıştır. Elde edilen sonuçlara göre öğretmen adaylarının kullandıkları stratejiler arasında model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Another study carried out by Cumhur and Korkmaz [42] suggested that pre-service primary school teachers mostly used the number line model, while the set model less. This may result from the fact that their abstract thinking and high-level thinking skills are developed by their age.…”
Section: Resultsmentioning
confidence: 99%
“…Another study carried out by Cumhur and Korkmaz [42] suggested that pre-service primary school teachers mostly used the number line model, while the set model less. This may result from the fact that their abstract thinking and high-level thinking skills are developed by their age.…”
Section: Resultsmentioning
confidence: 99%